EFEKTIVITAS MACROMEDIA FLASH DAN YOUTUBE DALAM PEMBELAJARAN PENDIDIKAN JASMANI PADA MASA COVID–19 DI KOTA PALANGKARAYA - Harvianto, Yudo (Jurnal Ilmiah Mandala Education (JIME), 2021)
The Coronavirus - 19 (Covid-19) pandemic has made all school programs from the curriculum section experience changes in learning. These changes lead to an online learning system (in a network) in the form of maximum use of technology. The pandemic requires all educators and students to enter the world of technology. One way to increase effectiveness is by utilizing information and communication technology (ICT) such as macromedia flash and youtube applications. Especially with the increasing advancement of technology globally today and the covid-19 pandemic, it is very important for a physical education educator to have good skills about information technology, so that it can be used as a learning medium. The main objective of this research is to know the effectiveness of macromedia flash and youtube in learning physical education during Covid-19 in the city of Palangka Raya. The research method used by researchers is experimental with pre-experimental design. Researchers used a quantitative approach in the implementation of this research. The experimental method in this research is used to measure the changes that occur after treatment. T test in this research using the Minitab application. The results of this research based on the T test for two paired samples showed P-Value <α (0.000 <0.05) so that Ho was rejected. Based on these results, it shows that the use of macromedia flash and youtube applications has a positive impact and is proven to be effective in improving student learning outcomes in physical education learning.